Simole matimatical technique in leaser cavity design and manufacturing - Baghdad Science Journal (مجلة بغداد للعلوم)
In this research design was treated gap laser mathematically and practically Bashaddam model Raasi simple and new and we have found that there is a good match in the practical and theoretical results